The Maltese cactus: an autoethnography of the colonization of desire. Issue 3 (3rd July 2019) - Rodríguez-Dorans, Edgar
ABSTRACT: This article presents an autoethnographic account of an encounter between two men – a Mexican scholar and a British artist – who met in Malta, to examine how post-colonialism influences the seemingly personal experience of erotic desire. The author, a man of indigenous descent, explores how his erotic attraction interweaved with powerful dynamics that were the product of the other man's European cultural background. He problematizes this attraction by reflecting on the white ethnocentrism that colored his partner-seeking process. This autoethnography analyzes how European colonialism in Mexico affected not only language and religion, but also the deceivingly intimate aspect of erotic desire.